An enabling framework as a holistic intervention to address physical developmental constraints in the Johannesburg inner city - Msingaphantsi, Mawabo (My University, 2015)
This research report demonstrates how an enabling framework can be applied as a means to address morphological issues in a manner that also fulfils certain existing urban policy objectives. The aim of the research is to assess the extent to which an enabling framework applied in this way can create environments that are in line with the core values of the urban design profession. The morphological issues in question are primarily due to the continued existence of the railway lines in the middle of the Johannesburg CBD. The policies in question, presented in the form of spatial development frameworks (SDFs), are those of the City of Johannesburg (COJ) and the Gauteng Provincial Government (GPG). The enabling framework is an approach to settlement making that is characterised by three aspects. The first is its end product, a movement-oriented spatial framework known as the organising concept. The second aspect is the enabling framework’s open ended approach, which holds that the city is an act of will: that a city can be shaped proactively by a single idea and that the idea need not be detailed in order for it to be applied. Lastly, the enabling framework is distinct in its understanding of participation, which is described as democratic feedback: an infinite number of responses to the organising concept that includes even the production of alternate plans. It is argued in this report that these three aspects of the enabling framework align well with the existing policy context in Johannesburg, where there is emphasis on spatial planning (with a strong transport component), on an open ended approach, and on participatory approaches to planning. The report assesses the extent to which the application of the enabling framework in this context can create an environment that espouses urban design principles. This is done in three steps: demonstrating how an enabling framework is constituted and how it may be applied; demonstrating possible responses to it; and then evaluating these responses on the basis of imageability (Lynch, 1975) and responsiveness (Bentley et al, 1985). In general, the findings from this assessment indicate that enabling frameworks may be more effective at addressing imageability than they are at creating responsiveness.
Thesis is submitted in partial fulfilment for the degree of Master of Urban Design to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2015
Keywords: Urban policy--South Africa--Johannesburg; Inner cities--South Africa--Johannesburg